Understanding and Modeling Förster-type Resonance Energy Transfer (FRET) FRET-Applications, Vol. 3 - Demir, Hilmi Volkan; Hernández Martínez, Pedro Ludwig; Govorov, Alexander; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This Brief will focus on the functional uses and applications of FRET, starting with the derivation of FRET in the assemblies of nanostructures and subsequently giving application cases for biologists, physicists, chemists, material scientists, engineers, and those in many other fields whoever would like to FRET as a tool. The goal of this part is therefore to show both specialist and non-specialist how to use and analyze FRET in a wide range of applications.
FRET overview -- Nonradiative energy transfer in assembly of nanostructures -- Applications of FRET -- Functional uses and analyses of FRET experiments -- Summary -- Appendix.
Keywords: Microtechnology; Microelectromechanical systems; Nanoscience; Nanotechnology; Electrical engineering; Electric power production; Microsystems and MEMS; Nanophysics; Nanotechnology; Electrical and Electronic Engineering; Electrical Power Engineering; Mechanical Power Engineering